Syndromic Indicators and Wastewater Surveillance of SARS-CoV-2 – A Population-Based Longitudinal Study from South India - Deodatt M. Suryawanshi; Vanamail Perumal; Suguna Anzbhagan; Divya Rajaseharan; Anupriya Asaithambi (Preventive Medicine: Research & Reviews)
Background: The COVID-19 pandemic has highlighted the need for effective surveillance systems to monitor and predict disease outbreaks. This study aims to investigate the relationship between syndromic indicators and wastewater surveillance for SARS-CoV-2 detection, with the goal of developing an early warning system for COVID-19. Materials and Methods: A longitudinal study was conducted from 11 July 2022 to 31 January 2023. Household data for syndromic indicators acute febrile illness (AFI), acute respiratory infection (ARI), influenza-like illness (ILI) and severe ARI were collected using a multistage sampling approach, and wastewater samples were gathered from 40 distinct locations across the city. Results: The incidence of ILI cases was significantly higher than other syndromic indicators (P < 0.01). A significant positive correlation was observed between AFI (r = 0.62), ARI (r = 0.47), ILI (r = 0.38) and wastewater SARS-CoV-2 positivity (WW SARS-CoV-2) (r = 0.82) with daily incident COVID-19 cases. Poisson regression analysis revealed that that AFI and WW SARS-CoV-2 were significant positive predictors of COVID-19 cases. Conclusion: Integrating AFI and WW SARS-CoV-2 into infectious disease surveillance will enhance effective outbreak prediction, pandemic response and outbreak management.